Resveratrol Alleviates Dextran Sulfate Sodium-Induced Acute Ulcerative Colitis in Mice by Mediating PI3K/Akt/VEGFA Pathway - Zhu, Fang; Zheng, Jujia; Xu, Fang; Xi, Yiyuan; Chen, Jun; Xu, Xiangwei (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a chronic inflammatory disease that affects the colon, and its incidence is on the rise worldwide. Resveratrol (RSV), a polyphenolic compound, was recently indicated to exert anti-inflammatory effects on UC. Consequently, the current study set out to investigate the mechanism of RSV on alleviating UC in mice by mediating intestinal microflora homeostasis. First, potential targets that RSV may regulate UC were screened using the TCMSP database. Next, mice were treated differently, specifically undergoing sham-operation, dextran sulfate sodium (DSS) induction, treated or untreated with RSV. Disease Activity Index (DAI) and HE staining were employed to analyze the pathological changes of mice colon. In addition, the expression patterns of inflammatory factors in spleen tissues were detected using ELISA, while the protein expression patterns of PI3K, Akt and VEGFA in colon tissues were determined by means of immunohistochemistry (IHC) and Western blot analysis. Moreover, changes in intestinal flora and metabolite diversity in UC were analyzed by metabonomics. It was found that RSV played inhibitory roles in the PI3K/Akt pathway in mice. Meanwhile, the administration of RSV induced down-regulated expressions of TNF-α, IFN-γ, IL-1β, IL-6, and IL-4. The six floras of Haemophilus and Veillonella were significantly enriched in UC, while Clostridium, Roseburia, Akkermansia and Parabacteroides were found to be enriched in control samples. Lastly, it was noted that Akkermansia could regulate the intestinal flora structure of UC mice through triacylglycerol biosynthesis, glycerol phosphate shuttle and cardiolipin biosynthesis and other metabolic pathways to improve UC in mice. Altogether, our findings indicate that RSV suppressed the activation of the PI3K/Akt pathway and reduced VEGFA gene expression to alleviate UC in mice.